The acceptances of tutor portal implementation at Shah Alam secondary schools / Mohd Nizam Mohamad Sharif - Mohamad Sharif, Mohd Nizam (2006)
The thesis statement for this research was the acceptances students on tutor portal implementation to students' social life and education. There were 2 reasons for this research. First, the researcher wanted to identify student characteristics toward tutor portal acceptances. Second, the researcher also wanted to determine the level of acceptances that influencing the student use on tutor portal application. One of the methods that were chosen by the researcher in order to carry out this study was a survey. About 120 of students were selected randomly to be the sample. The respondents were given a week to fill up the questionnaires. Then, the collected data were analyzed using the Microsoft Word, Microsoft Excel and SPSS applications software. As a result, it was found that tutor portal program did affect students' education. Students lost lots of energy and their social life had also been changed. From the research, it was revealed that tutor portal program was the most ICT education learning used by the students. There were some solutions that could be taken to increase perception and acceptances school community about the ICT learning. The school community could raise awareness and motivation on whole School institution includes teacher activities center. Education resources center, education district center and etc. Finally, campaigns on the consciousness of ICT learning should be held throughout the whole education enviroments